The safety of remimazolam versus propofol in gastroscopic sedation: a meta-analysis - Xincan An; Tianqi Shen; Xingxing Yin; Jin Xu; Yongming Zhang; Tianlong Wang (BMC Anesthesiology, 2024)
Abstract Background This meta-analysis was designed to compare the safety and efficiency of remimazolam with those of propofol in patients undergoing gastroscope sedation. Methods We searched PubMed, Cochrane Library, Embase, Ovid, Wanfang Database, China National Knowledge Infrastructure, SINOMED, and ClinicalTrials.gov for studies that reported on remimazolam versus propofol for gastroscope sedation from establishment to February 25, 2023. The sedative efficiency and the incidence of adverse events were assessed as outcomes. Version 2 of the Cochrane risk-of-bias assessment tool was used to assess the risk of bias. Review Manager 5.4 and STATA 17 were used to perform all statistical analyses. Results A total of 26 randomized controlled trials involving 3,641 patients were included in this meta-analysis. The results showed that remimazolam had a significantly lower incidence of respiratory depression (risk ratio [RR] = 0.40, 95% confidence interval [CI]: 0.28–0.57; p < 0.01, GRADE high), hypoxemia (RR = 0.34, 95% CI: 0.23–0.49; p < 0.01, GRADE high), bradycardia (RR = 0.34, 95% CI: 0.23–0.51; p < 0.01, GRADE high), dizziness (RR = 0.45, 95% CI: 0.31–0.65; p < 0.01, GRADE high), injection site pain (RR = 0.06, 95% CI: 0.03–0.13; p < 0.01, GRADE high), nausea or vomiting (RR = 0.79, 95% CI: 0.62–1.00; p = 0.05, GRADE moderate), and hypotension (RR = 0.36, 95% CI: 0.26–0.48; p < 0.01, GRADE low). Conclusions Remimazolam can be used safely in gastroscopic sedation and reduces the incidence of respiratory depression, hypoxemia, bradycardia, injection site pain, and dizziness compared with propofol, and doesn't increase the incidence of nausea and vomiting.